(untitled) (Journal of the College of Languages (JCL), 2016)
Writing in English is one of the essential factors for successful EFL learning .Iraqi students at the preparatory schools encounter problems when using their background knowledge in handling subskills of writing(Burhan,2013:164).Therefore, this study aims to investigate the 4thyear preparatory school students’ problems in English composition writing, and find solutions to these problems through a suggested schematic language learning strategy training approach dealing with writing problems .The researcher made a survey at eight preparatory schools of AL-Risafa (1) General Directorate of Education :(316) from the scientific branch (159 males &157 females) and (284) from the literary branch (145 males &139 females), in Baghdad, during the second term of the academic year 2014-2015.In this regard, a suitable questionnaire is designed and exposed to a jury of specialists in ELT. The results indicate that the subjects of the study,i.e.preparatory school students are poor in English composition writing due to poor teaching methods, students’lack interest in vocabulary, grammar knowledge ,cultural knowledge, and schema .Then, the study advocates that writing problems can be reduced to a minimum if students are taught by using schema .With this orientation, this study suggests a schematic language learning strategy training that enables students to overcome their writing problems by developing their linguistic schema, formal schema and content schema .Conclusions, recommendations ,and suggestions are made.